Institute of adoption in comparative law - Krstinić Dalibor M.; Vasiljković Jovana Z. (Strani pravni život, 2020)
The subject of research in this paper is the analysis of institute of adoption, which is the most important form of family protection for children without parental care and is based on the establishment of a kinship relationship between the child and the new parents. Adoption is a social, legal and emotional process that enables children who cannot be raised by biological parents and relatives to become, legally and permanently, members of the adoptive family. On the basis of the above, the relevance of the adoption institute is evident, and particular attention will be paid to comparative analysis of the provisions governing it in various legislations. The aforementioned implies the aim of the paper, which is a comparative overview of the adoption institute according to the solutions contained in the positive Swiss, German, French and Russian legislation. As a concluding consideration, we will summarize the legal regulation governing the institution of adoption in the selected legislation.